EVALUASI PENERAPAN BUILDING INFORMATION (BIM) 5D TERHADAP WAKTU REVIEW UNTUK OPTIMALISASI WAKTU DAN BIAYA - rio hamdani (Racic : Rab Construction Research, 2020)
RIO HAMDANI, NIM 1410246101. Evaluation of the Implementation of Building Information (BIM) 5D on Review Time For Optimizing Time And Costs, supervised by Sigit Sutikno and Manyuk Fauzi. Design review efficiency to obtain the changes order document is very important to be completed at the beginning of the project and not overlapping to the implementation schedule. One cause of the addendum or CCO is a drawings error that use 2D CAD software suchas mismatches design, design changes, specification changes, design errors and drawings that are less detailed and complete so that it affects the work schedule and material purchases. This research was conducted using a descriptive qualitative approach where data were obtained from interviews and questionnaires on four competent personnel both from the contractor and construction management consultants to then be compared with data obtained from BIM practitioners. With this research it is proven that the use of BIM greatly helps the efficiency of review time so that it affects the overall project time achievements. The efficiency of review time can be achieved by 52.94%, the calculation of volume and cost can be improved by 42%. While the cost efficiency and number of personnel are 9% and 9.5%. Keywords: Time, Efficiencies, Reviews, BIM